“Democratizing” artificial intelligence in medicine and healthcare: Mapping the uses of an elusive term - Rubeis, Giovanni; Dubbala, Keerthi; Metzler, Ingrid (Frontiers in Genetics, 2022)
Introduction ‘Democratizing’, in the context of medical AI, can be seen as a vague term that encompasses various meanings, issues, and narratives. Criticism has been raised referring to ‘democratization’ as a buzzword. In this article we map the ways in which the term is used in discourses on Artificial Intelligence (AI) in medicine and healthcare. Methods We searched literature from Scopus, Google Scholar, and PubMed along with grey literature using search terms “democrat*”, “artificial intelligence” and “machine learning”. We analyzed selected literature to address the questions - What is the object of democratization? What should be democratized, and why? What kind of theory of democracy is tied to specific narratives? And who is the demos who is said to benefit from democratization? Results We identified four clusters of visions of democratization: 1) democratizing healthcare through AI 2) democratizing access to AI technologies and use 3) democratizing access to and oversight of data 4) making AI an object of the rule by the people. Democratization is mostly defined as easy access that can be achieved through technological fixes and free-market solutions. Socio-political implications such as rights, citizenship, and equity, are largely ignored. Discussion ‘Democratization’ in the context of AI in healthcare needs a theory of citizenship, deliberative processes and modes of participation to ensure that those affected by healthcare AI have a say in decision-making. A concept of equity is essential to ensure that access is granted not only to developers and health professionals but also to patients.